The Effect of Debt Financing on Firm Profitability of Manufacturing Companies in Malaysia. - Hazaratul Liza, Hasan; Zaidi, Nurul Syuhada; Mohamed, Ahmad Syubaili; Suzila, Binti Mohamed Yusof; Nazaria, Md. Aris (Human Resource Management Academic Research Society, 2021)
Debt financing has grown rapidly in recent year. Debt financing is one of the common ways for company to increase their capital to run their business. This study focuses on the debt financing towards firm profitability of manufacturing companies listed in Bursa Malaysia. By applying trade-off theory and pecking order theory, this study predicts there are significant relationship on debt financing towards firm profitability. This research would further collect debt financing data of listed manufacturing companies in Malaysia and analyse the relationship by descriptive analysis and regression analysis. This study used 23 companies to determine the debt financing towards firm profitability of the listed manufacturing companies in Malaysia. The data was taken for the period of 8 years which were from 2010 to 2018. The independent variables were debt ratio, long term debt and short-term debt while the dependent variable was the return on equity and used to measure the firm’s performance. The findings will be useful for policymaker and listed manufacturing companies in Malaysia to make better debt financing decisions. Findings of this research will also aid in maintaining an optimum capital structure and maximize the stockholder’s wealth of the listed manufacturing companies in Malaysia.